1998
DOI: 10.1146/annurev.biochem.67.1.335
|View full text |Cite
|
Sign up to set email alerts
|

Rna Localization in Development

Abstract: Cytoplasmic RNA localization is an evolutionarily ancient mechanism for producing cellular asymmetries. This review considers RNA localization in the context of animal development. Both mRNAs and non-protein-coding RNAs are localized in Drosophila, Xenopus, ascidian, zebrafish, and echinoderm oocytes and embryos, as well as in a variety of developing and differentiated polarized cells from yeast to mammals. Mechanisms used to transport and anchor RNAs in the cytoplasm include vectorial transport out of the nuc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
193
0
7

Year Published

1999
1999
2009
2009

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 321 publications
(202 citation statements)
references
References 247 publications
(414 reference statements)
2
193
0
7
Order By: Relevance
“…One mechanism for achieving protein asymmetry is to localize the mRNA encoding the protein. This mechanism is widely used in a number of cellular processes, such as fibroblast motility and synaptic plasticity in neurons Singer 1997, 2001;Bassell et al 1999), embryogenesis in Drosophila (Bashirullah et al 1998;Lipshitz and Smibert 2000), and mating-type switching in yeast Saccharomyces cerevisiae (Long et al 1997;Takizawa et al 1997).…”
mentioning
confidence: 99%
“…One mechanism for achieving protein asymmetry is to localize the mRNA encoding the protein. This mechanism is widely used in a number of cellular processes, such as fibroblast motility and synaptic plasticity in neurons Singer 1997, 2001;Bassell et al 1999), embryogenesis in Drosophila (Bashirullah et al 1998;Lipshitz and Smibert 2000), and mating-type switching in yeast Saccharomyces cerevisiae (Long et al 1997;Takizawa et al 1997).…”
mentioning
confidence: 99%
“…La localisation des ARN dépend de déterminants de séquence présents sur ces ARN [10]. Les élements importants de ces déterminants peuvent être soit des structures secondaires et tertiaires plus ou moins complexes, soit des régions simple brin dont la séquence est alors critique.…”
Section: Mécanismes Généraux De Localisation Des Arnmunclassified
“…The perfect example is the discovery and the studies of the function of localized RNAs. The first localized mRNAs were discovered over 2 decades ago in the oocytes of Drosophila fly and Xenopus frog (Rebagliati et al, 1985;Frigerio et al, 1986); then over 100 different localized RNAs have been found in unicellular organisms and in various cell types of animal and plant species (Bashirullah et al, 1998;King et al, 1999;Lipshitz and Smibert, 2000;Jansen, 2001;Kloc et al, 2001Kloc et al, , 2002Zhou and King, 2004;.…”
Section: Introductionmentioning
confidence: 99%
“…The simplest and most widely accepted explanations for the biological function of mRNA localization phenomenon include: (1) to assure the high-level synthesis of protein encoded by localized mRNA at the site where it is needed the most and (2) to prevent the protein from being synthesized in the region of the cell where it is not needed or could have a harmful effect (Bashirullah et al, 1998;King et al, 1999;Lipshitz and Smibert, 2000;Jansen, 2001;Kloc et al, 2002). Thus, the assumption has always been that the only function of mRNA (localized and unlocalized) is to make a protein.…”
Section: Introductionmentioning
confidence: 99%